2017
DOI: 10.18520/cs/v112/i08/1675-1689
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone-Based Aryloxypropanolamine as a Potential Antidiabetic and Antidyslipidaemic Agent

Abstract: The hybrid congener 3 derived from hydroxychalcone and pharmacophore oxypropanolamine for adrenergic receptor, along with its enantiomers 9a and 9b were selected from a series of compounds for detailed studies of their antidiabetic profile in sucrose-challenged, low-dosed, streptozotocin-induced diabetic rats and in db/db mice, and antidyslipidaemic profile in high fat diet-induced dyslipidaemic hamsters. The test compounds exhibited significant and consistent antidiabetic and antidyslipidaemic activities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Several authors have evaluated the antihyperglycemic activity of synthetic chalcones in streptozotocin-induced diabetic rats ( Satyanarayana et al, 2004 ; Shukla et al, 2007 ; Najafian et al, 2010 ; Rawat et al, 2011 ; Mahapatra et al, 2017a ; Sengupta et al, 2017 ; Shukla et al, 2017 ; Tajammal et al, 2017 ; Acharjee et al, 2018 ; Naidu, 2018 ; Raju et al, 2018 ). It was found that these compounds have a moderate to potential ability to reduce blood sugar.…”
Section: Preclinical Pharmacological Activities Of Chalconesmentioning
confidence: 99%
“…Several authors have evaluated the antihyperglycemic activity of synthetic chalcones in streptozotocin-induced diabetic rats ( Satyanarayana et al, 2004 ; Shukla et al, 2007 ; Najafian et al, 2010 ; Rawat et al, 2011 ; Mahapatra et al, 2017a ; Sengupta et al, 2017 ; Shukla et al, 2017 ; Tajammal et al, 2017 ; Acharjee et al, 2018 ; Naidu, 2018 ; Raju et al, 2018 ). It was found that these compounds have a moderate to potential ability to reduce blood sugar.…”
Section: Preclinical Pharmacological Activities Of Chalconesmentioning
confidence: 99%
“…Compound 189 (0.92 µM) is a trihydroxy chalcone that is effective against diabetes as it inhibits AMP-kinase activity [ 243 ]. A chalcone with an aryloxy propylamine unit ( 190 ) has been reported as an effective antidiabetic agent, inhibiting type 2 diabetes in rats [ 244 ]. Compound 191 shows good inhibitory activity against PTP1B [ 245 ].…”
Section: Chalcones For Non-infectious Diseasesmentioning
confidence: 99%
“…Chalcones are important precursors for the natural flavonoid biosynthesis [22] and they are also used in various synthetic manipulations for diverse enzyme targets. The chalcones with varied substitutions at different positions have been explored for combating a wide variety of pathological conditions such as in diabetes, [23–25] cancer, [26–28] inflammation, [29,30] cardiac disorders, [31] malaria, [32] oxidative stress and also active against certain type of infections like viral, bacterial and fungal [33–37] . They also offer a wide spectrum of CNS actions including inhibition of acetylcholinesterase (AChE) and butyrylcholinestrase (BuChE), activity on GABA receptor, anti‐depressant, anxiolytic activity, anti‐Alzheimer properties and monoamine oxidase inhibition [38,39] …”
Section: Synthetic Approaches and Design Aspects Of Various Classes Omentioning
confidence: 99%